Radiological Patterns of Pulmonary Tuberculosis and their Association with Clinical, Microbiological, and Hematological Parameters - ullah Jan, Rahmat; Natarajan, Satheesh Babu; Ali, Nasir (Journal of Neonatal Surgery, 2025)
Background and Objective: Pulmonary tuberculosis (PTB) exhibits some parameters of clinical, microbiological, and laboratory variability that can be associated with radiologic involvement of the lungs. These associations can enhance prompt identification and treatment, which is primarily applicable to comorbid patients. Thus, this paper evaluated the radiological distribution of lung involvement in the suspected PTB patients and investigated the correlation among the radiological distribution with the demographic characteristics, clinical manifestations, microbiological findings, blood hematological and fasting blood sugar concentrations. Methodology: This analytical research was undertaken in institute of Basic Medical Sciences (IBMS), Khyber Medical University in a cross-sectional manner. One hundred three (n=103) patients with pulmonary tuberculosis and aged over 18 years were involved and divided into three categories based on the chest radiographs: upper (n = 35), middle (n = 31) and lower (n = 37) zone pulmonary involvement. Demographic information, clinical symptoms, medical history, and comorbidity was noted. Microbiological tests involved the differential counts of bronchoalveolar lavage, cytology, Gramme staining, Ziehl-Neelsen staining and AFB culture. Hematological parameters (TLC and ESR) and fasting blood sugar levels were measured. Continuous variables were analyzed using Kruskal Wallis test, and categorical variables using Chi-square or Fisher’s exact test. Results: The study findings showed that the mean age of patients was an insignificantly associated across the three groups (upper: 49.88 ± 13.6 years; middle: 49.71 ± 13.71 years; lower: 50.0 ± 12.12 years; p=0.981). Cough was reported in 103(100%) and fever was present in 34 (97.1%) patients with upper zone involvement, 30 (96.8%) with middle zone involvement, and 36 (97.3%) with lower zone involvement, showing no significant difference among the groups (p=1.000). Cytology and AFB culture, showing no significant differences among radiological groups. Fasting blood sugar was elevated in 31(83.8%) patients with lower zone involvement, compared to 10(28.6%) in the upper zone and 11(35.5%) in the middle zone (p<0.001). Conclusion: This study concluded that radiological lung involvement in TB is mainly independent of demographic, clinical, microbiological, and hematological parameters, with the exception of a strong association between lower zone disease and diabetes mellitus...